Peer-Assessment's Effect on Improving EFL Students' Speaking Performance - Sulhah, Siti; Oktaviana, Fadilla (Foremost Journal, 2024)
Speaking is the most difficult ability to learn in English due to surroundings such as English classrooms as well as other contexts prevent students from speaking in the language. The current research should establish how much peer assessment improves EFL students' abilities to speak. Therefore, with the aim to determine whether or not EFL students' speaking skills were improving, the researchers conducted an experimental study using a peer assessment approach. This study included twenty-five first-graders of MTS Daarul Ulum Panyaungan in Lebak-Banten. Data from the evaluation of the study, interviews, observations, and field notes were analyzed. The mean pupil score before applying peer review was 60; nevertheless, after implementing peer evaluation, the mean student score improved to 75. The post-test demonstrated an enhancement in speaking abilities after using peer assessment. Peer evaluation can assist EFL students improve their speaking skills. The study found that adopting peer assessment helps EFL students accomplish better during speaking. Since this research suggests that peer assessment enhances speaking skills significantly, additional research is definitely needed, especially for EFL students. The researcher suggests more studies to develop new peer evaluation methods and to apply peer evaluation in EFL students in a variety of ways.